From Polymer to Magnetic Porous Carbon Spheres: Combined Microscopy, Spectroscopy, and Porosity Studies - Cesano, Federico; Cravanzola, Sara; Brunella, Valentina; Damin, Alessandro; Scarano, Domenica (Frontiers in Materials, 2019)
The facile preparation of polymer waste-derived microporous carbon microspheres (SBET800 m2/g) 100-300 μm in size, is reported at first. We have taken advantage of both, the crosslinked nature and the porous texture of the poly(4-ethylstyrene-co-divinylbenzene) microspheres, which allow the incoming anions and cations present in liquid media to enter and to remain segregated into the pores of the polymer microspheres as soon as the solvent is removed. Interestingly, the ZnCl2 phase, when incorporated in the microporous molecular architecture of the polymer, prevents the collapsing of the pore structure of thermosetting polymer spheres during the pyrolysis occurring at 800°C and acts as an activating agent of the carbon phase under formation, being responsible for the formation of an extended mesoporosity (30-200 Å and 300-1000 Å ranges). More interestingly, porous carbon microspheres with magnetic properties have been prepared from the ZnCl2-activated porous carbon spheres after impregnation with Fe nitrate solution and thermal treatment at 800°C. A multi-technique methodology to characterize more extensively the carbons at the micro/nanoscale is reported in the paper. More in detail, the morphology, structure, porous texture and the surface properties of the carbon and of the magnetic carbon microspheres have been investigated by scanning and transmission electron microscopy, atomic force microscopy, X-ray diffraction, N2 physisorption, diffuse reflectance UV-vis, Raman and infrared spectroscopies. Furthermore, magnetic properties have been revealed at the nano- and at the macroscale by magnetic force microscopy and simple magnetically guided experiments by permanent magnets. The multi-technique methodology presented in the paper allows in elucidating more extensively about the different characteristics of activated carbons. Notwithstanding the huge amount of literature on activated carbons, the precise control of both the structure and the surface has, for the most part, hidden the relevance of other properties at the molecular scale of the assembled architectures. On the other hand, recent studies indicate that by molecular design, nanostructured and porous carbonaceous materials could also be rationally proposed.